Fluorescence studies of new potential antitumoral indole derivatives in lipid membranes - Castanheira, Elisabete M. S. (2008)
This work was funded by FCT and FEDER through CFUM and CQ-UM, project POCI/QUI/59407/2004 and post-Doc grant (SFRH/BPD/24548/2005) of A.S.A